1976
DOI: 10.1147/rd.202.0148
|View full text |Cite
|
Sign up to set email alerts
|

Drop Formation from a Liquid Jet: A Linear One-dimensional Analysis Considered as a Boundary Value Problem

Abstract: Using a one-dimensional model, the author studied drop formation using a boundary value perturbation, rather than a spatially periodic one as considered by Rayleigh. The Rayleigh solution becomes the high jet velocity approximation to this linear analysis. At lower velocities the analysis shows that the medium becomes dispersive, and drop formation characteristics are quite different from that predicted by Rayleigh. In an appendix, the gross momentum balance and flow rate conservation are used to consider drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 6 publications
1
27
1
1
Order By: Relevance
“…To understand their significance, one has to consider the full problem in halfspace, with boundary conditions at the nozzle. This was attempted in a series of papers (Pimbley, 1976;Bogy 1978aBogy , 1978bBogy , 1979b, which correctly analyzed the problem for large Weber numbers. However, the authors failed to notice the absolute instability later found by Leib and Goldstein (1986) for small ␤.…”
Section: B Spatial Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…To understand their significance, one has to consider the full problem in halfspace, with boundary conditions at the nozzle. This was attempted in a series of papers (Pimbley, 1976;Bogy 1978aBogy , 1978bBogy , 1979b, which correctly analyzed the problem for large Weber numbers. However, the authors failed to notice the absolute instability later found by Leib and Goldstein (1986) for small ␤.…”
Section: B Spatial Instabilitymentioning
confidence: 99%
“…This allowed him to look at the nonuniformity of breakup and to estimate the size of satellite drops. Lee's equations were further investigated (Pimbley, 1976;Pimbley and Lee, 1977) to study satellite behavior. The fundamental problem with Lee's equations is, however, that viscosity will become important in the process of pinching, regardless of how small.…”
Section: One-dimensional Approximationsmentioning
confidence: 99%
“…By application of the continuity principle to a control volume bounded by two contiguous cross-sections and the corresponding interface, the following result is obtained: Before pursuing the matter further, it would be pertinent to introduce some considerations on the assumption of the unidimensionality of the problem. This assumption is well justified in capillary jets whenever the ratio of the disturbance wavelength to the undisturbed radius of the jet is large (Pimbley 1976;Pimbley & Lee 1977). In the liquid bridge, a typical wavelength perturbation is determined by the bridge length, and the abovementioned ratio is of the order of twice the slenderness A, which is bounded from above by the value A = n.…”
Section: One-dimensional Slice Inviscid Modelmentioning
confidence: 99%
“…The classical breakup driven by the Rayleigh mechanism [19] is caused by the amplification of shape defects due to surface tension effect. Unlike the classical breakup, the forced breakup that is influenced by the discharge velocity modulation based on the Pimbley's theoretical analysis [20] is dominantly caused by the periodical inertial dynamics of the liquid jet. While in the case of passive modulation, where especially acoustic resonance is employed [21], [22], relatively small depth of modulation is achieved and technically significant increase in erosive effects has not been proven yet, significant progress has been achieved using methods of an active flow modulation around the nozzle.…”
Section: Experience With Generating Pulsed Liquid Jet Gathered So Farmentioning
confidence: 99%